Akseptasi Pedagang Tradisional Terhadap Penggunaan Mesin EDC Perbankan di Pasar Tradisional Ikon Wisata Belanja di Surakarta - Nuryuda Irdana; Handayani Rahayuningsih; Maulida Chairunnisa R. V (Sekolah Vokasi, Universitas Gadjah Mada, 2018)
Nowadays, some of traditional markets have become as an icon in tourism destination. Shopping is an activity that relatively closed to tourism. There is a traditional market which relatively popular and already known as shopping tourism icon in Surakarta, that is Klewer market. The number of transactions and sales volume that occur in this market is estimated reach out until billion rupiahs.In this era, the utilization of technology change the character of tourists. The development of banking technology can reduce the used of cash money. In doing the tour, tourists mostly bring less cashes. But, they usually have debit or credit cards to support their transactions. Bank responses this fact by deploying EDC machines at traditional markets to support the transaction. However, there are some merchants that still enjoy doing transaction by cash and reluctant to use EDC machine. The aims of this research is to find out the criteria that prioritized by merchants in assessing the use of EDC machine in Surakarta shopping tourism traditional market. Klewer as location was determined through purposive method by the reason as shopping tourism icon of Surakarta. This research used non-probability and purposive sampling techniques to get the samples. AHP (Analytical Hierarchy Process) model was used in this research as analysis method. The result of this research showed that the Surakarta traditional market merchants acceptance in using banking EDC machine is affected by usefulness, ease of use and security. The criteria which prioritized by merchants in assessing the use of EDC machine from the most to least are usefulness, ease of use and security which have almost equal weight.